Opsoclonus Myoclonus - Scarff, Jonathan R. (Matrix Medical Communications, 2011)
Opsoclonus myoclonus is a rare autoimmune condition characterized by cerebellar degeneration. It occurs most often as a paraneoplastic syndrome when a cancer remote to the brain induces cerebellar dysfunction that is unrelated to metastases. Half of all cases occur in children with a neuroblastoma. Most adults with opsoclonus myoclonus have neoplastic, infectious, metabolic, or idiopathic etiologies. Signs of cerebellar dysfunction noted at presentation include opsoclonus, myoclonus and ataxia, hence the name “dancing eyes, dancing feet syndrome.” Opsoclonus is characterized by rapid, involuntary eye movements that are dysrhythmic and uncoordinated. Neuronal damage is induced by antibodies usually related to the primary pathology. Treatment targets the etiology and also employs steroids, plasmapheresis, immunosuppressive agents, or other anti-inflammatory therapies. Children with opsoclonus myoclonus resulting from a neuroblastoma often retain neurological sequelae. Adult cases of opsoclonus myoclonus with idiopathic or infectious etiologies have a more favorable prognosis than those with neoplastic origins.